The effect of the thermophoretic force on diffusion of dust particles in cryogenic plasma - Muratov, M.M.; Moldabekov, Zh.A.; Aldakulov, E.; Ramazanov, T.S.; Temirbek, A.M. (Recent Contributions to Physics, 2019)
At cryogenic temperatures of atoms, the thermophoretic force (atomic drag force) is stronger than at room temperature. The temperature difference between the surface of the dust particles and the surrounding gas was previously evaluated. This difference was the reason of the manifestation of the so-called thermophoretic force between dust particles. This paper presents the results of a study obtained using molecular dynamics modeling of the effect of thermophoretic force on the mean-square displacement of charged dust particles in a two-dimensional layer. The mean-square displacement (MSD) characterizes the diffusion of particles. By changing parameters that describe thermophoretic force, there were identified cases when this force leads to significant changes in the properties of the cryogenic complex plasma. Also the data on computer simulation are provided. MSD was calculated for different values of the coupling parameter. The ratios MSD curves with and without thermophoretic force are given. It was found that the thermophoretic force can drastically influence the diffusion of dust particles if the characteristic interaction radius due tothermophoretic force exceeds the average distance between dust particles. The aforementioned effect can take place at low density of neutral and temperatures relevant to cryogenic conditions. The force with increasing value of cutoff raduis causes deviation of the curves from data obtained on the basis neglecting thermophoretic force. Deviation becomes more visible, with increasing coupling parameter, due to the force.